Encyclopedia of Life Sciences 2015
DOI: 10.1002/9780470015902.a0003307.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Lung Development

Abstract: Early respiratory development begins with the specification of the lung cell fate, followed by the emergence of lung buds from the ventral foregut endoderm. The respiratory tree is then elaborated through branching morphogenesis, and proliferation and differentiation of specialised cell types along the proximal–distal axis produces airways and alveoli, respectively. Lung development is orchestrated through crosstalk between the epithelium and the mesenchyme; morphogenesis and differentiation of the lung relies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The respiratory progenitors are identified by expression of the transcription factor Nkx2-1 , which is the earliest known marker of lung specification, along the ventral foregut endoderm. Following specification, lung morphogenesis ensues with the formation of two primary buds that evaginate into the surrounding splanchnic mesoderm at E9.5, followed by elaboration of the conducting airways through branching morphogenesis (Havrilak and Shannon, 2015a; Herriges and Morrisey, 2014; Metzger et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The respiratory progenitors are identified by expression of the transcription factor Nkx2-1 , which is the earliest known marker of lung specification, along the ventral foregut endoderm. Following specification, lung morphogenesis ensues with the formation of two primary buds that evaginate into the surrounding splanchnic mesoderm at E9.5, followed by elaboration of the conducting airways through branching morphogenesis (Havrilak and Shannon, 2015a; Herriges and Morrisey, 2014; Metzger et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…Events in early lung development are driven by reciprocal tissue interactions between the mesenchyme and the epithelium (Havrilak and Shannon, 2015a; Hines and Sun, 2014; McCulley et al, 2015; Shannon et al, 1998). These interactions are mediated by diffusible paracrine factors, and intensive research over the past two decades has identified many of the conserved signaling pathways governing early lung specification and morphogenesis.…”
Section: Introductionmentioning
confidence: 99%